Exploratory and Confirmatory Factor Analysis of PERMA for Chinese University EFL Students in Higher Education - Yang, Lan; Mohd, Rashid Bin Saad (Universitas Negeri Makassar, 2021)
The purpose of this research is mainly to explore the validity and reliability of PERMA instruments to determine the nature of PERMA for Chinese university EFL students. A total of 309 Chinese university EFL students from 10 universities in Gansu province were investigated. Selected by cluster random sampling, the extracted data from the survey design underwent exploratory factor analysis(EFA) and confirmatory factor analysis(CFA) with the use of SPSS version 24 and AMOS version 23 to verify the factor structure of the PERMA. The results of EFA indicate similar structures from prior research and the present study. The CFA results testify that the PERMA instrument is satisfactory for Chinese university EFL students. Therefore, this research indicates that the PERMA of Chinese university EFL students also has a five-factor structure, which implies the perceived PERMA in the Chinese EFL context to be adequately invariant and it as an effective measurement tool supporting the research of Chinese university students’ well-being. The findings highlight the significance of validating and confirming the PERMA structure and provide new insights into its application across different cultural contexts.